Quercetin Induces Apoptosis via Downregulation of Vascular Endothelial Growth Factor/Akt Signaling Pathway in Acute Myeloid Leukemia Cells - Shi, Huan; Li, Xin-Yu; Chen, Yao; Zhang, Xing; Wu, Yong; Wang, Zi-Xuan; Chen, Pan-Hong; Dai, Hui-Qi; Feng, Ji; Chatterjee, Sayantan; Li, Zhong-Jie; Huang, Xiao-Wei; et al. (Frontiers in Pharmacology, 2020)
Acute myeloid leukemia (AML) is an aggressive haematological malignancy characterized by highly proliferative accumulation of immature and dysfunctional myeloid cells. Quercetin (Qu), one kind of flavonoids, exhibits anti-cancer property in multiple types of solid tumor, but its effect on acute myeloid leukemia is less studied, and the underlying mechanisms still largely unknown. This study aimed to explore the specific target and potential mechanism of quercetin-induced cell death in AML. First, we found that quercetin induces cell death in the form of apoptosis, which was caspase-dependent. Second, we found that quercetin-induced apoptosis depends on the decrease of mitochondria membrane potential (MMP) and Bcl-2 proteins. With quantitative chemical proteomics, we observed the downregulation of VEGFR2 and PI3K/Akt signaling in quercetin-treated cells. Consistently, cell studies also identified that VEGFR2 and PI3K/Akt signaling pathways are involved in the action of quercetin on mitochondria and Bcl-2 proteins. The decrease of MMP and cell death could be rescued when PI3K/Akt signaling is activated, suggesting that VEGFR2 and PI3K/Akt exert as upstream regulators for quercetin effect on apoptosis induction in AML cells. In conclusion, our findings from this study provide convincing evidence that quercetin induces cell death via downregulation of VEGF/Akt signaling pathways and mitochondria-mediated apoptosis in AML cells.